Preliminary Evidence of Human Plasmodium in Domestic Animals from a Malaria-Endemic Region in Indonesia [version 4; peer review: 2 approved, 1 approved with reservations, 1 not approved] - Munirah Munirah; Sitti Wahyuni; Firdaus Hamid; Isra Wahid (F1000Research)
Background In Indonesia, malaria incidence is at a high rate despite maximum preventive efforts. Therefore, this study aims to determine the possibility of a Plasmodium reservoir among domestic animals in malaria-endemic areas. Methods Animal blood was collected using EDTA tubes, then smeared and stained with Giemsa for Plasmodium microscopic identification. About 10 μl of blood was dropped on to a filter paper to capture Plasmodium DNA. Nested PCR was used for parasite molecular detection, while Plasmodium species were identified using the sequenced DNA. Results A total of 208 and 62 animal blood samples were collected from Gaura village, West Sumba and Fakfak village, West Papua, Indonesia respectively. In total, 32 samples from Gaura contained P. falciparum or P. vivax, while the Plasmodium percentage in buffalo, horse, goat, and dogs were 20.7%, 14.3%, 5.8%, 16.7%, respectively. P. knowlesi was not found in any of the samples, and no other species were detected in 18 pig blood samples. Conclusion The human Plasmodium DNA in domestic animals within malaria-endemic regions suggests a potential link to the persistence and high prevalence of malaria in these areas. While the findings suggest a potential role of domestic animals in malaria transmission, they remain preliminary and do not definitively establish domestic animals as reservoirs. Further research is necessary to confirm these findings and to better understand the contribution of domestic animals to the transmission dynamics of malaria.